2019
DOI: 10.1186/s13012-018-0849-z
|View full text |Cite|
|
Sign up to set email alerts
|

Hospital organizational context and delivery of evidence-based stroke care: a cross-sectional study

Abstract: BackgroundOrganizational context is one factor influencing the translation of evidence into practice, but data pertaining to patients with acute stroke are limited. We aimed to determine the associations of organizational context in relation to four important evidence-based stroke care processes.MethodsThis was a mixed methods cross-sectional study. Among 19 hospitals in Queensland, Australia, a survey was conducted of the perceptions of stroke clinicians about their work using the Alberta Context Tool (ACT), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…Organisational culture has repeatedly been identified as an important factor influencing EBP (Andrew et al, ). Our study results demonstrated that EBP organisational culture and readiness were the strongest factors of the total Quick‐EBP‐VIK score.…”
Section: Discussionmentioning
confidence: 99%
“…Organisational culture has repeatedly been identified as an important factor influencing EBP (Andrew et al, ). Our study results demonstrated that EBP organisational culture and readiness were the strongest factors of the total Quick‐EBP‐VIK score.…”
Section: Discussionmentioning
confidence: 99%
“…The ACT draws on the Promoting Action on Research Implementation in Health Services framework that considers context, evidence, and facilitation as the three key concepts for research implementation (Kitson, Harvey, & McCormack, 1998;McCormack et al, 2002;Rycroft-Malone, 2004). It has been primarily applied in Canadian long-term care (Estabrooks et al, 2015;Knopp-Sihota, Niehaus, Squires, Norton, & Estabrooks, 2015;Slaughter & Estabrooks, 2013) and pediatric hospital settings (Squires et al, 2013;Yamada, Squires, Estabrooks, Victor, & Stevens, 2017) with individual studies conducted in Europe (Eldh, Ehrenberg, Squires, Estabrooks, & Wallin, 2013;F€ orberg et al, 2014;Hoben, Estabrooks, Squires, & Behrens, 2016;Seers et al, 2018) and Australia (Andrew et al, 2019;Schultz & Kitson, 2010).…”
Section: Emergency Nurse Surveymentioning
confidence: 99%
“…A qualitative study of clinicians' perspectives on barriers and facilitators to implementing rehabilitation guidelines for patients with stroke found that time and resources were important contextual factors that affected guideline implementation (Munce et al, 2017). In a cross-sectional study of 19 Australian hospitals it was identified that working in higher compared to lower context environments (measured using the ACT) was associated with improved stroke care (Andrew et al, 2019). An analysis of 36 Canadian nursing homes showed that facilities with higher context scores (assessed using the ACT) had a significantly lower prevalence of dyspnoea, pain, and urinary tract infections in nursing home residents (Estabrooks et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following publication of the original article [1], the authors reported an error in one of the authors’ names. In this Correction the incorrect and correct author name are shown.…”
mentioning
confidence: 99%